2009
DOI: 10.2981/07-096
|View full text |Cite
|
Sign up to set email alerts
|

Prey and Prey‐Age Preference by the Iberian Wolf Canis Lupus Signatus in a Multiple‐Prey Ecosystem

Abstract: In many regions of the Iberian Peninsula, wild ungulates have disappeared and wolves Canis lupus often depend on garbage dumps and domestic animals. This paper represents an example of wild ungulate preferences of the Iberian wolf Canis lupus signatus in an environment with no human‐wildlife conflicts, because wolves rarely predate on livestock. I studied the patterns of prey selection by the Iberian wolf during May 1998‐October 2002 in northwestern Spain, in an area which supports a diverse community of wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
74
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 26 publications
10
74
0
6
Order By: Relevance
“…Wolves in the Superior National Forest, Minnesota, prey primarily on white-tailed deer (Odocoileus virginianus) fawns during summer (Kunkel and Mech 1994;Nelson and Mech 1986;Van Ballenberghe et al 1975). Roe deer (Capreolus capreolus) fawns and wild boar (Sus scrofa) piglets constitute the main prey in some areas of the Iberian Peninsula and Italy during summer (Barja 2009;Capitani et al 2004). Ungulates less than 40 kg such as blackbucks (Antilope cervicapra) represent the main prey of wolves in India (Jethva and Jhala 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Wolves in the Superior National Forest, Minnesota, prey primarily on white-tailed deer (Odocoileus virginianus) fawns during summer (Kunkel and Mech 1994;Nelson and Mech 1986;Van Ballenberghe et al 1975). Roe deer (Capreolus capreolus) fawns and wild boar (Sus scrofa) piglets constitute the main prey in some areas of the Iberian Peninsula and Italy during summer (Barja 2009;Capitani et al 2004). Ungulates less than 40 kg such as blackbucks (Antilope cervicapra) represent the main prey of wolves in India (Jethva and Jhala 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the area south of the Douro river, an almost monospecific diet was found, with the domestic goat (Capra hircus Linnaeus, 1758) as the main prey. Several studies have demonstrated the importance of increasing the abundance of wild prey, in order to reduce the impact of wolf on livestock, thereby reducing conflicts with humans (Cuesta et al 1991, Vos 2000, Barja 2009, Meriggi et al 2011. Therefore, in due course, the reintroduction of roe deer in central Portugal would provide a source of wild prey for the Iberian wolf, decreasing wolf livestock predation, thus reducing conflicts with humans (Treves & Karanth 2003, Treves et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…This method, however, is time-intensive, and therefore it is often desirable for scat collection to be directed to areas of higher scat concentration such as dens , on roads (Barja 2009), or where wolves are known to have been recently (e.g., through back tracking in snow). To test if there was a difference in the results from different scat-sampling methods used in our study (homesite versus road collection, see Chapter 3), we used the G-test (Sokal and Rohlf 1994) in STATA (Stata Corporation, v9.2, College Station, TX).…”
Section: Chapter 5: Conclusionmentioning
confidence: 99%
“…Scat analysis was pioneered in Alaska by and remains the most widely used method to quantify wolf diet. As a result, wolf diet has been quantified in every corner of their range, from Arizona to Greenland, Spain to Mongolia, and back to north-western Alaska (e.g., Merkle et al 2009, Marquard-Peterson 1998, Barja 2009, Van Duyne et al 2009, Stephenson and James 1982. Many accuracy issues and biases have been addressed throughout the wide application and long history of scat analysis, but no research has addressed how results may differ, depending on where scats are sampled.…”
Section: Chapter 5: Conclusionmentioning
confidence: 99%
See 1 more Smart Citation